Synergistic dual-functional full deionization and electrocatalysis of water by ZnO/Ti3C2Tx heterojunction supported with novel template - Chao Huang; Guanghui Zhan; Zhaohui Xiao; Shiwei Lin (Next Materials)
Electrochemical water splitting faces challenges related to cost and efficiency, prompting researchers to develop new materials for cost reduction and efficiency enhancement. MXene Ti3C2Tx, with its large surface area and excellent conductivity, shows promising prospects for catalytic applications. Electrochemists have successfully utilized MXene Ti3C2Tx in catalysis, leveraging its ability to form heterojunction structures that enhance charge transfer and separation. In contrast, inexpensive metal oxide semiconductors encounter limitations such as harsh reaction conditions, instability, and low activity in electrochemical water splitting. Recent studies indicate that delaminated ultra-thin MXene Ti3C2Tx materials exhibit improved conductivity and larger surface area compared to the original MXene Ti3C2Tx. Theoretically, incorporating these ultra-thin MXene Ti3C2Tx materials with inexpensive metal oxide materials could overcome performance limitations. In this study, we developed a method for growing ZnO nanorods on a foam nickel substrate through an in-situ hydrothermal process, followed by coating with ultra-thin MXene Ti3C2Tx. This approach resulted in dual-functional electrocatalytic performance for both the oxygen evolution reaction and hydrogen evolution reaction. Notably, the prepared ZTNF catalyst demonstrated exceptional stability, with overpotentials of 260.3 mV for HER and 343.4 mV for OER at a current density of 10 mA/cm2. The Tafel slopes measured were 123.5 mV/dec for HER and 41.7 mV/dec for OER, highlighting the superiority of ZTNF over other catalyst materials in this research field. Overall, this study demonstrates the significant potential of metal oxide semiconductors and MXene Ti3C2Tx composite materials in the field of electrocatalysis.